An application of Barnacle Mating Optimizer in Infectious Disease Prediction: A Dengue Outbreak Cases - Mustaffa, Zuriani; Sulaiman, Mohd Herwan; Mohsin, Mohamad Farhan Mohamad; Yusof, Yuhanis; Ernawan, Ferda; Yusob, Bariah; Noor, Noorhuzaimi Mohd (Iraqi Journal of Science, 2020)
Meta-heuristic algorithms have been significantly applied in addressing various real-world prediction problem, including in disease prediction. Having a reliable disease prediction model benefits many parties in providing proper preparation for prevention purposes. Hence, the number of cases can be reduced. In this study, a relatively new meta-heuristic algorithm namely Barnacle Mating Optimizer (BMO) is proposed for short term dengue outbreak prediction. The BMO prediction model is realized over real dengue cases data recorded in weekly frequency from Malaysia. In addition, meteorological data sets were also been employed as input. For evaluation purposes, error analysis relative to Mean Absolute Percentage Error (MAPE), Mean Square Error (MSE), and Mean Absolute Deviation (MAD) were employed to validate the performance of the identified algorithms which includes the comparison between BMO against Moth Flame Optimizer (MFO) and Grey Wolf Optimizer (GWO) algorithms. Upon simulation, the superiority is in favour to BMO by producing lower error rates.